Review of rare bird species in the North Kazakhstan: update and additions to the regional avifauna list - Ivan A. Zuban; Alexey Y. Timoshenko; Pavel S. Dmitriyev; Sergey N. Gashev; Mikhail N. Kalashnikov; Bakhytzhan M. Suindykov; Vladislav S. Lunyov; Stanislav V. Shnel (Acta Biologica Sibirica, 2025)
The study details long-term observations conducted in the North Kazakhstan region from 2016 to 2024, focusing on bird species that were either previously unrecorded or rarely encountered. The research clarified data on the occurrence and seasonal activity of specific species by analyzing unpublished observations and recent publications. A notable outcome was the addition of six new species to the regional avifauna list, enhancing our understanding of local bird diversity. These findings underscore the dynamic nature of bird populations and the potential impacts of ecological and climatic changes. Key factors contributing to the registration of new species include climate change and habitat transformation. The results highlight the importance of ongoing biodiversity monitoring in light of global changes.